Entre ausencia y presencia (2020)
This project is part of the material relevant to the work of grade to opt for the title of master in fine arts and Visual of the Antonio Nariño University. This material involves an academic text (this text), a book artist, and an exhibition. Between Absence and Presence, is an academic text of research-creation, which investigates, from contemporary artistic practices, the relationship between life and death, through the presence of my mother. Its structure orders the different moments that the artistic project goes through; at first it feeds on the log; a travel journal that records reflexive gestures and some poetic texts. In the second moment, images of art and history are analyzed, in addition to genealogical photographs; a third moment is the creation of a laboratory, exercise of external observation, and fourth phase the final materialization. From a personal perspective, outlining multiple definitions of a chair; a space, a body, a road, a sound or a presence, concepts and meeting points between figure mother, my father, and the Act of walking, part of the process of my artistic practice. Continue the resulting definitions above categories, each category deals with personal reflections and images type historical, genealogical, and memory, introduced as related artistic and historical scenarios. Shows plastic gestures and reflections: an approach to materials, drawings, photographs, or sound pieces that become of inquiries. Finally; as a result of the performed process, define the approach of the creation and realization of the plastic work.